2016
DOI: 10.1002/2211-5463.12131
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular cloning, heterologous expression, and enzymatic characterization of lysoplasmalogen‐specific phospholipase D from Thermocrispum sp.

Abstract: Lysoplasmalogen (LyPls)‐specific phospholipase D (LyPls‐PLD) is an enzyme that catalyses the hydrolytic cleavage of the phosphoester bond of LyPls, releasing ethanolamine or choline, and 1‐(1‐alkenyl)‐sn‐glycero‐3‐phosphate (lysoplasmenic acid). Little is known about LyPls‐PLD and metabolic pathways of plasmalogen (Pls). Reportedly, Pls levels in human serum/plasma correlate with several diseases such as Alzheimer's disease and arteriosclerosis as well as a variety of biological processes including apoptosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 62 publications
1
17
0
1
Order By: Relevance
“…The substrate specificity of rLyPls‐PLD was in the order: LyPlsCho (100%) > Lyso‐PAF (53%) ≫ LyPlsEtn (0.16%) ( Table ); the activity toward 1‐palmitoyl‐2‐hydroxy‐ sn ‐glycero‐3‐phosphocholine (16:0 LPC) was 3.9% as previously reported . These results suggested that LyPls‐PLD perhaps recognized the choline head group and sn ‐1 chain.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…The substrate specificity of rLyPls‐PLD was in the order: LyPlsCho (100%) > Lyso‐PAF (53%) ≫ LyPlsEtn (0.16%) ( Table ); the activity toward 1‐palmitoyl‐2‐hydroxy‐ sn ‐glycero‐3‐phosphocholine (16:0 LPC) was 3.9% as previously reported . These results suggested that LyPls‐PLD perhaps recognized the choline head group and sn ‐1 chain.…”
Section: Resultssupporting
confidence: 78%
“…LyPls‐PLD is a member of the glycerophosphodiester phosphodiesterase (GDPD; EC3.1.4.46) family . Shi et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations